The complete chloroplast genome sequence of Passiflora xishuangbannaensis (Passifloraceae), a vine endemic to Yunnan, China - Chunhui Hao; Fuchuan Wu (Mitochondrial DNA. Part B. Resources, 2021)
Passiflora xishuangbannaensis, Passiflora subgenus Decaloba, is a very rare endemic to the Yunnan, China. Here we report and characterize the complete chloroplast (cp) genome sequence of P. xishuangbannaensis to provide genomic resources useful for promoting its conservation and systematics. The complete genome is 135,742 bp in length and the overall GC content is 37.1%. The cp genome sequence has a typical quadripartite structure, comprising two inverted repeats (IRs: 20,604 bp) regions, which are separated by a small single-copy (SSC: 13,159 bp) region and a large single-copy (LSC: 81,375 bp) region. Moreover, a total of 122 functional genes were annotated, including 77 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenetic analysis recovered P. xishuangbannaensis as a member of subgenus Decaloba.